NO IS NOT ENOUGH : DEFEATING THE NEW SHOCK POLITICS - NAOMI KLEIN (UK ALLEN LANE, 2017)
No Is Not Enough reveals, among other things, how Trump's election was not a peaceful transition, but a corporate takeover, one using deliberate shock tactics to generate wave after wave of crises and force through radical policies that will destroy people, the environment, the economy and national security. This book is the toolkit for shock resistance, showing all of us how we can break Trump's spell and win the world we need.
Keywords: POLITIC AND GOVERNMENT-UNITED STATE; POLITICAL CULTURE; DONALD TRUMP